The Diagnostic Value of the Thermostatic Amplification of Ribonucleic Acid in Bronchoalveolar Lavage Fluid in Smear-Negative Pulmonary Tuberculosis - Wu, Zhengxing; Shi, Jichan; Zhou, Yueying; Pan, Ning; Qiu, Chaochao; Wu, Lianpeng; Jiang, Xiangao (Frontiers in Public Health, 2022)
Objective This study aimed to determine the value of the simultaneous amplification and testing for Mycobacterium tuberculosis in bronchoalveolar lavage fluid (BALF) in the diagnosis of smear-negative pulmonary tuberculosis (PTB). Methods A total of 316 patients were selected, of which 197 had smear-negative PTB (observation group), and 119 did not have TB (control group). Bronchoscopy was performed in both groups, and BALF samples were collected for acid-fast bacilli smears, simultaneous amplification/testing for TB (SAT-TB), and BACTEC MGIT 960 cultures. The sensitivity, specificity, positive predictive, and negative predictive values of SAT-TB in BALF for the diagnosis of negative TB were calculated. Results The sensitivity of SAT-TB detection was 45.18%, which was significantly higher than smears and slightly lower than cultures. The specificity of SAT-TB was 99.16%, which differed slightly from the other two methods. The positive predictive value was 98.89%, which was not significantly different from the other two methods. The negative predictive value of SAT-TB was 58.91%, which was higher than smears and slightly lower than cultures. Conclusion The very high specificity and negative prediction of SAT-TB in BALF means that the method has great application value for the rapid diagnosis of smear-negative PTB.